Penerapan Prinsip Transparansi Pengelolaan Keuangan Desa: Investigasi di Desa Sambo - Ika Helsa; Syamsul Syamsul (Universitas Veteran Bangun Nusantara, 2022)
This research aims to explore the application of transparency principles in village financial management. This type of research is qualitative research. This research was conducted in Sambo Village, South Dolo District, Sigi Regency. The data used is primary data obtained through open interviews with the Village Government, Village Officials, Village Consultative Body (BPD), and the Community. The research results illustrate that the principle of transparency is starting to be applied at every stage of village financial management. At the planning stage, it is realized in the form of deliberations and billboards. The implementation stage is realized in the form of involvement of the BPD in implementing the work program and budget. Finally, at the reporting and accountability stage, the application of the principle of transparency is realized in the form of involvement of the BPD in preparing the Village APB realization and accountability report, submitting the report to the sub-district, and direct delivery to the community through the Village APB accountability meeting.